The Eucharist in medieval canon law - Izbicki, Thomas M. 1945- (Cambridge Cambridge University Press, 2015)
Thomas Izbicki presents a new examination of the relationship between the adoration of the sacrament and canon law from the twelfth to fifteenth centuries. The medieval Church believed Christ's glorified body was present in the Eucharist, the most central of the seven sacraments, and the Real Presence became explained as transubstantiation by university-trained theologians. Expressions of this belief included the drama of the elevated host and chalice, as well as processions with a host in an elaborate monstrance on the Feast of Corpus Christi. These affirmations of doctrine were governed by canon law, promulgated by popes and councils; and liturgical regulations were enforced by popes, bishops, archdeacons and inquisitors. Drawing on canon law collections and commentaries, synodal enactments, legal manuals and books about ecclesiastical offices, Izbicki presents the first systematic analysis of the Church's teaching about the regulation of the practice of the Eucharist.
The sacraments in Medieval canon law -- The real presence of Christ, the minister, and the materials of the sacrament -- The form of the sacrament and the elevation of the host -- Communion: union with Christ and unity in the sacrament -- Custody of the Eucharist and communion of the sick -- Corpus Christi and wonder hosts
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 900-1550; Lord's Supper -- History, Middle Ages, 600-1500.; Canon Law -- History, To 1500 -- Sources; Canon Law -- History -- To 1500 -- Sources; Lord's Supper -- History -- Middle Ages, 600-1500; Lord's Supper ; History ; Middle Ages, 600-1500; Canon law ; History ; To 1500 ; Sources